A Review of the Research on Mongolia’s Perception of China (Journal of International Studies, 2021)
Mutual perception is an important indicator of the degree of closeness between countries, and it can more intuitively reflect the degree of mutual favorability between the two peoples and the perception of each other's national image. Mongolia's perception of China is an important fundamental aspect in the bilateral relations. This article reviews and examines the current research status of the given topic in academic circles. In general, (1) The public opinion surveys of some research institutes on Mongolia’s perception of China are relatively objective and neutral, so their survey results have higher reference value and application value. (2) Regarding the specific studies of Mongolia’s perception of China, some studies are relatively neutral, objective and of keen insights, and some are difficult to divorce from the perspective of the ‘self’ or the western interpretation mode, often presuppose their positions and tend to place too much emphasis on historical and cultural factors. Mongolia's perception of China is the result of the interaction of various factors mainly including history, emotion/psychology, realistic issues, and external factor.Хятадын талаарх монголчуудын ойлголтын тухай судалгааны тоймХураангуй: Монголчуудын Хятадын талаарх ойлголтын тухай асуудал бол хоёр улсын харилцааны чухал сэдвийн нэг байдаг. Энэхүү өгүүлэл нь академик судалгааны хүрээнд уг сэдвийн судалгааны өнөөгийн байдлыг ангилан дүгнэж харуулах юм. Ерөнхийдөө: (1) судалгааны байгууллагуудын монголчуудын Хятадыг танин мэдэх ойлголттой холбоотой тоо баримт санал асуулга харьцангуй бодитой, тийм учраас судалгааны үр дүн хэрэглээний ач холбогдол өндөр гэж үзэж болно. (2) Хятадын талаарх монголчуудын ойлголтын тухай нарийвчилсан судалгаанаас харахад, зарим судалгаа харьцангуй бодитой төвийг сахисан, гүнзгийрүүлж судалсан байдаг ч зарим судалгаа нь нэг талыг барьсан, соёл хоорондын мөргөлдөөний онолоор тайлбарлаж, анхнаасаа байр суурь дүгнэлт нь тодорхой, хэт түүх соёлын хүчин зүйлийг дөвийлгөсөн шинжтэй байдаг. Монголчуудын Хятадыг танин мэдэх ойлголт нь түүх, сэтгэл зүй, бодит нөхцөл байдал, гадаад хүчин зүйлс зэргийн харилцан үйлчлэлийн үр дүнд бүрэлдсэн юм.Түлхүүр үгс: Монгол, Хятадыг танин мэдэх ойлголт, судалгаа, онцлог